Identification Factors Associated with Elderly Health Status at the Godean Primary Health Center, Yogyakarta - Indriani, I; Fatmawati, Veni; Mulyono, Dhinda Prakusya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The study aims to determine the general health status among elderly and attempts to identify its determinants at Godean Primary Health Center Yogyakarta, Indonesia. This cross-sectional study used primary data of elderly people included age 45 years old and older (n=362), 78 subjects enrolled in this study were selected base on a purposive sampling design and factors affecting health status and the relationship to health status were identified by Kendall Tau Test. Furthermore, health status measurements were obtained through interviews, while characteristics data were evaluated using instruments. We found that majority elderly (56,4%) had bad general health status, while 35,9% had Hypertension, 3,8% had Diabetes Mellitus (DM) and 6,4% had both hypertension and DM. Age and employment status were determinant factors for elderly health status (p=<0.05). It is concluded that necessary to evaluate and improve health promotion programs at Godean Primary Health Center to collaborate with village officials to carry out strengthening monthly regular health checks.